Quantum chemical modelling, molecular docking, synthesis and experimental anti-microbial activity of 1,4-diazepan linked piperidine derivative - Khushbu Agrawal; Tarun M. Patel; Shavi Thakur; Kruti Patel; Sumit Mittal (SpringerOpen, 2024)
Abstract Background In this work, we represent synthesis, in silico analysis and biological activity of 1,4 diazepine linked piperidine derivatives (6a-6o). All the derivatives were screened for their anti-microbial activity against gram-positive (Staphylococcus aureus, Bacillus Subtills, Bacillus megaterium) and gram-negative (Escherichia coli, Pseudonymous, Shigella sp.) bacteria. Compounds were synthesized from reaction of tert-butyl 1,4-diazepane-1-carboxylic, butyryl chloride and varied aromatic aldehyde, further characterized by 1H NMR and LCMS spectral techniques. Result Using ampicillin as a positive control, the synthetic compounds 6a-6o were tested for their in-silico study and experimental anti-microbial activity against gram-positive (Staphylococcus aureus, Bacillus Subtills, Bacillus megaterium) and gram-negative (Escherichia coli, Pseudonymous, Shigella sp.) bacteria. According to in vitro assay compound 6a, compound 6c, compound 6d, compound 6m and compound 6I showed higher activity against all the tested strains. Molecule 6i, compound 6j, compound 6k, compound 6f has good to moderate antibacterial activity. DFT computations were used to optimize the molecular geometry at the B3LYP/6-31G (d, p) theoretical level. The corresponding energy values of molecular orbitals were visualized using optimized geometries. Moreover, Auto Dock Vina 1.2.0 is used to assess molecular docking against two target proteins, Bacillus subtilis (PDB ID: 6UF6) and Protease Vulgaris (PDB ID: 5HXW). The target molecule 6b displayed the best binding energies for both. Additionally, we calculated the ADME for each molecule (6a-6o). Conclusion All fifteen synthesized compounds were screened for their in vitro and in silico analysis. In vitro analysis for anti-microbial activity was carried out against gram-positive (Staphylococcus aureus, Bacillus Subtills, Bacillus megaterium) and gram-negative (Escherichia coli, Pseudonymous, Shigella sp.) bacteria and compound 6a, compound 6c, compound 6d, compound 6m and compound 6I exhibits more potent activity towards all tested strains. Molecular docking is performed against target proteins, L-amino acid deaminase from Proteus Vulgaris and LcpA ligase from Bacillus subtilis, representing the Gram-negative bacterium and Gram-positive bacterium, respectively. Compound 6b showed the highest no. of interaction with protein according to molecular docking. With the advent of innovative techniques like ADME, we select their hit compounds early on and anticipate future pharmacokinetic and pharmacodynamic benefits and drawbacks of these promising therapeutic candidates. Graphical abstract